Blockchain regulation and governance in Europe / Michèle Finck. - Finck, Michèle, 1986- (Cambridge University Press, 2019)
In Blockchain Regulation and Governance in Europe, Michèle Finck examines the relationship between blockchain technology and EU law and introduces the theme of blockchain governance. The book provides a general introduction to blockchains as both a regulatable and a regulatory technology and outlines the interaction between distributed ledger technology and specific areas of EU law, such as the General Data Protection Regulation. It should be read by anyone interested in EU law, the relationship between law, innovation and technology, and technology governance.